Implementation of ADC in VLSI using AFPWM - Prasad Tripathy, Hara; Pattanaik, Priyabrata; Kumar Kamilla, Susanta (International Journal of Psychosocial Rehabilitation, 2025)
An integral part of sensor and potential applications is an analog to digital converter (ADCs). The realization of ADC by using “Pulse Width Modulation (PWM)” has been discussed in this work. A reference signal is required by this technique for comparing sampled input signal in analog format for generating “pulse width modulated signals”. This ADC offers an advantage of extension to multiple sampling simultaneously. A cheap system based on microcontroller is built by this application. These designs are also characterised by low latency and fast response which makes them useful in biomedical applications in measuring single or multiple inputs.